ANALISIS KEBUTUHAN BIMBINGAN PSIKOSOSIAL TERHADAP KLIEN DEWASA TINDAK PIDANA NARKOTIKA DI BALAI PEMASYARAKATAN KLAS. II GARUT - Pertiwi, Regita Mauldi; Simanjuntak, Meitisa Vanya (Journal of Mental Health and Social Rehabilitation, 2025)
This thesis disscuses the factors of adult clients of narcotics crimes committing narcotics abuse based on social psychological theory to design a new guidance program proposal by paying attention to the client's psychosocial factors. This research is a descriptive study with qualitative research methods. Data collection was done by interviews, observation, and literature study. The research took up the place at Garut Class II Probation and Parole Office. Research subjects are determined using purposive sampling technique, which is determined on the basis of certain objectives that have a close relationship with the problem, namely 1) Head of Adult Client Guidance Subsection; 2) Probation Officer and 3) Correctional Client as the drug users. The data validity technique uses cross check from the results of interviews and literature study. The data analysis used was inductive analysis with the following steps: 1) data reduction, 2) data presentation, 3) conclusion. The result of this research found that there is an effect from the environment on a person's personality that can lead to narcotic abuse behavior. Behavior was obtained through the process of social learning. Individuals with low self-control and resilience (self efficancy) easily affected by negative environmental conditions that can make any violations such as drug abuse. The proposed programs of the narcotics crime client that can be implemented by the Garut Class II Probation and Parole Office are psychoeducation, family counseling, improvement of the client's economic welfare and community socialization.